Efeitos imediatos e tardios da imersão em água pós-exercício: uma revisão sistemática e um ensaio clínico randomizado - Machado, Aryane Flauzino [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Background: Cold water immersion (CWI) is a technique commonly used in post-exercise recovery. However, the procedures involved in the technique may vary, particularly in terms of water temperature and immersion time, and the most effective approach remains unclear. Purpose: To determine the efficacy of CWI in pain management compared with passive recovery. We also aimed to identify which water temperature and immersion time provides the best results. Methods: MEDLINE, EMBASE, SPORTDiscus, PEDro and The Cochrane Library databases were searched up to January 2015. Only randomized controlled trials that compared CWI to passive recovery were included in this review. Results: Nine studies were included in the review and meta-analysis. The results of meta-analysis revealed that CWI has a more positive effect than passive recovery in terms of immediate (WMD=0.290, 95% CI [0.037, 0.543]; p=0.025) and delayed effects (WMD=0.315, 95% CI [0.048, 0.581], p=0.021). The pooled of studies that used water temperature of between 10-15°C demonstrated the best results for immediate (WMD=0.273, 95% CI [0.107, 0.440], p=0.001) and delayed effects (WMD=0.317, 95% CI [0.102, 0.532], p=0.004). In terms of immersion time, immersion of between 10-15 minutes had the best results for immediate...
Keywords: Fisioterapia; Crioterapia; Dor musculoesquelética; Imersão; Fisiologia; Physical therapy